2006
DOI: 10.4028/www.scientific.net/amr.11-12.575
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Nanocrystalline Copper Powders by Aqueous Reduction

Abstract: This paper aims at a simple preparation method of nanocrystalline copper powders through copper sulfate reduction by potassium borohydride in aqueous solution. The product powders obtained in various conditions were investigated by X-ray powder diffraction, transmission electron microscope and particle size distribution analyzer. The parameters that influence the preparation process of copper crystalline were researched, such as the effect of complexing agent, the molar ratio of copper sulfate to potassium bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Among the diverse methods, laser sintering method and high-energy ball milling method involve strict process conditions, more money invest and more energy consumption and lower productive rate [5,6]. The sonochemistry is characterized by a quick reaction rate, yet research stays at the stage of laboratory, but it has shown broad prospect of industrialization because of its simple equipment and short technological process [7,8]. Considering that growing needing of superfine metal paritcles in recent years, an economical superfine metal particles preparation method is required.…”
Section: Introductionmentioning
confidence: 99%
“…Among the diverse methods, laser sintering method and high-energy ball milling method involve strict process conditions, more money invest and more energy consumption and lower productive rate [5,6]. The sonochemistry is characterized by a quick reaction rate, yet research stays at the stage of laboratory, but it has shown broad prospect of industrialization because of its simple equipment and short technological process [7,8]. Considering that growing needing of superfine metal paritcles in recent years, an economical superfine metal particles preparation method is required.…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous reduction method is of better utility value [7][8][9][10][11]. In this experiment, polyaniline were produced on the surface of nano copper, nano copper particles were be wrapped completely, nano copper composite was obtained with good capability and configuration.…”
Section: Introductionmentioning
confidence: 99%